Zad2 oblicz
a) (2^ -1+3^ -1)^ -1=...
b) (-0,5)^ -2-0,3^ -3-1^ -5=...
c) (4/5)^ -1+(-2i2/3)^ -2=...
d) [-(1/2)^ -2-(1i3/5)^ -1*(-8) ] / (29^0-10^ -2) = ...

zad4
zapisz w postaci potegi i oblicz .
a) ((-1,2)^2)^ -1 = ...
b) (((3i12/17)^5)^0)^ -11 = ...
c) (((-2,49)^1)^ -1)^ -1 = ...
d) ((-1/2)^2)^ -1 * (-1/2) = ...

2

Odpowiedzi

2010-02-24T22:42:52+01:00
Zad2 oblicz
a) (2^ -1+3^ -1)^ -1=(½ + ⅓)⁻¹=(3/6 + 2/6)⁻¹=(5/6)⁻¹=6/5
b) (-0,5)^-2-0,3^-3-1^-5=2²-(10/3)³-1= 4-1000/27-1=
=3-1000/27=81/27-1000/27=-919/27-34 1/27
c) (4/5)^ -1+(-2i2/3)^ -2=5/4+(-8/3)⁻²=5/4+(-3/8)²=5/4+9/64=
=80/64+9/64=89/64
d) [-(1/2)^ -2-(1i3/5)^ -1*(-8) ] / (29^0-10^ -2) =
[-2²-2-(5/8)*(-8)] / 1-(1/100) = [-4-2+5] / 99/100= -1/ 99/100 =
=-100/99=-1 1/99
Zad 4
a) ((-1,2)^2)^ -1 = (-1,2)⁻²= (-6/5)⁻² = (-5/6)² =25/36
b) (((3i12/17)^5)^0)^ -11 = 1
c) (((-2,49)^1)^ -1)^ -1 = -2,49
d) ((-1/2)^2)^ -1 * (-1/2) = (-1/2)⁻² * (-1/2)¹=(-1/2)⁻¹=-2
2010-02-24T22:51:34+01:00
A) (2⁻¹+3⁻¹)⁻¹=(½+⅓)⁻¹=(3/6+2/6)⁻¹=(5/6)⁻¹=6/5
b) (-0,5)⁻²-(0,3)⁻³-1⁻⁵=(-1/2)⁻²-(3/10)⁻³-1⁻⁵=2²-(10/3)³-1=
4-1000/27-1=3-1000/27=3-37 1/27=-34 1/27
c)(⅘)⁻¹+(-2 ⅔)⁻²=5/4+(-8/2)⁻²=5/4+(-4)⁻²=5/4+1/16=20/16+ 1/16=21/16
d)[-(½)⁻²-(1 3/5)⁻¹*8]:(29°-10⁻²)=[-(4)-(5/8)*8]:(1+1/100)=[-4-5]:101/100=(-9)*100/101=-900/101
a) ((-1,2)²)⁻¹=(-1,2)¹=-1,2
b) (((3 12/17)⁵)⁰)⁻¹¹ =( 3 12/17)⁻⁶=(63/17)⁻⁶=(17/63)⁶
c) (((-2,49)¹)⁻¹)⁻¹ = (-2,49)⁻¹=(-100/249)
d) ((-1/2)²)⁻¹ * (-1/2) = (-1/2)¹*(-1/2)¹=¼